Review of lamivudine dosing in patients on combination antiretroviral therapy with renal impairment among hospitalised HIV infected patients at the university teaching hospital, Lusaka, Zambia\ - Mushina,Jonas (Lusaka: .University teaching hospital, the university of Zambia, School of medicine, 2016)
Drug errors in renal impairment are quiet common and could result in drug toxicity and poor patient outcome. This study, reviewed Lamuvidine dosing in renally impaired HIV hospitalised patient on combination antiretroviral therapy(CART) at the university teaching hospital (UTH).
A dissertation report submmited as partial fulfilment for the award of bachelor of pharmacy degree of the university of Zambia.
Keywords: Acquired immunodeficiency syndrome-drug therapy